1989
DOI: 10.1159/000226722
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Tissue Trace Metal Levels in Lung Cancer

Abstract: Copper, zinc, magnesium, calcium and iron were measured in serum and lung tissue – tumor mass and histologically nonneoplastic tissue – from lung cancer patients and compared with serum concentrations in healthy subjects and control lung tissue obtained from patients with nonmalignant lung disease. Lung cancer patients showed a significant increase in serum Cu and Cu/Zn ratio levels and decrease in serum Zn and Fe concentrations. These findings were correlated with TNM stage of the disease, but not with histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 3 publications
4
105
0
1
Order By: Relevance
“…A unique feature of cancer cells is to accumulate high concentrations of copper. It was previously reported that certain types of organiccopper complexes are capable of apoptosis induction that is not a result of oxidative effects [22]. Therefore, the capability of organic copper to induce apoptosis, the necessity of copper for angiogenesis, and the accumulation of copper by cancer cells and tissues allows for a novel therapeutic strategy focusing on elevated copper as a selection mechanism against cancer cells and tissues.…”
Section: Biochemical Determinationsmentioning
confidence: 99%
“…A unique feature of cancer cells is to accumulate high concentrations of copper. It was previously reported that certain types of organiccopper complexes are capable of apoptosis induction that is not a result of oxidative effects [22]. Therefore, the capability of organic copper to induce apoptosis, the necessity of copper for angiogenesis, and the accumulation of copper by cancer cells and tissues allows for a novel therapeutic strategy focusing on elevated copper as a selection mechanism against cancer cells and tissues.…”
Section: Biochemical Determinationsmentioning
confidence: 99%
“…Having these important physiologic functions, it is not surprising that the concentrations of both zinc and copper are tightly regulated in an organism (Maverakis et al, 2007;Labbe and Thiele, 1999). Interestingly, disturbed zinc homeostasis and the elevated copper level have been reported in many types of cancer, including breast, prostate, lung, and brain (Geraki et al, 2002;Nayak et al, 2003;Diez et al, 1989;Yoshida et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…High serum and tissue levels of copper have been observed in a variety of human tumors including brain (21), breast (22)(23), colon (24), lung (25), and prostate (24,26). In 1980, it was first noticed that Cu played a critical role in angiogenesis (27).…”
Section: Coppermentioning
confidence: 99%